The EFFECTIVENESS OF COGNITIVE BEHAVIOR THERAPY (CBT) GROUP CONSELING WITH SELF-INSTRUCTION TECHNIQUES TO REDUCE INSECURE FEELINGS OF STUDENTS CLASS VIII A AT MTs NURUL IMAN SUKOJATI BANYUWANGI: EFEKTIVITAS KONSELING KELOMPOK PENDEKATAN COGNITIVE BEHAVIOR THERAPY (CBT) DENGAN TEKNIK SELF-INSTRUCTION UNTUK MENGURANGI PERASAAN INSECURE SISWA KELAS VIII A di MTs NURUL IMAN SUKOJATI BANYUWANGI - Nur Muhammad Rohim; Heriberthus Wicaksono,; Ratna Wulandari, (Program Studi Bimbingan dan Konseling, 2023)
The research was conducted to determine the effectiveness of group counseling Cognitive Behavior Therapy (CBT) approach with Self-instruction technique to reduce insecure feelings of class VIII A students at MTs Nurul Iman Sukojati BanyuwangiThis study used a quasi-experiment with a one group pretest and posttes design. The research sample was selected using nonprobability sampling design technique using purposive sampling. The sample selection obtained 6 students from a total of 30 students who were categorized as high insecure feeling questionnaire scores. The data collection techniques used were insecure feeling questionnaire and observation. Researchers used data analysis techniques with the Statistical Program For Social Sciences (SPSS) 2.5 for windows 11 test obtained a t value of 8.253, which means that there has been a decrease in students' feelings of insecurity. With df = n-1 obtained df = 5 at a significant level of 5% then obtained t table 2.015, meaning t count> t table (8.235> 2.015). Thus it can be concluded that Ha which reads